AL-INSAN, AL-NAS DAN AL-BASHAR DALAM AL-QURAN - Maftuh Maftuh (MIYAH : Jurnal Studi Islam, 2020)
Abstrak: Thinking about humans in Arabic termed by the words al-insan, al-nas and al-bashar is an arduous endeavor because humans are creatures created by Allah swt. Although there are already various sciences that study and research about humans such as Biology, Embryology, Psychology, Anthropology, but no one has been able to unravel the mysteries of humans. al-insan can be interpreted as a creature who has the ability to reason, a knowledgeable creature and a civilized being. Although in other aspects it also contains elements of negative meaning. The term al-nas means that humans are created as social beings, starting from a male and female pair, then developing into tribes and nations, to get to know each other. As social beings, humans naturally like to live in groups, from the smallest unit (family) to the largest and most complex, namely the nation and mankind. The word al-Bashar shows the general similarities that are the main characteristics of humans, by describing humans as biological beings who have biological characteristics such as eating, drinking, sexual relations, etc. The naming of this word shows the meaning that biologically dominant humans are in their skin. This aspect shows the general biological differences between humans and animals, which are more dominated by fur or hair.Keyword: humans, al-insan, al-nas, al-bashar